On the Representation of the Object-Agreement Phrase - Motapanyane, Virginia (Papers from the Annual Meetings of the Atlantic Provinces Linguistic Association (PAMAPLA) / ACTES DES COLLOQUES ANNUELS DE L’ASSOCIATION DE LINGUISTIQUE DES PROVINCES ATLANTIQUES (ACAALPA)., 1992)
This paper is concerned with the internal structure of clauses containing past participle forms in Romance languages. We adopt the representation proposed in current literature to account for clauses with compound tenses, and we question its explanatory power when it comes to distinguish between an active verb in 'passe composé' and a passive construction. The improvement we propose consists in the representation of the argumental positions allowed in structures with a past participle inflection.